Bowling tournament / Suzaina Ismail - Ismail, Suzaina (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
A charity bowling tournament was or-ganised by Universiti Teknologi MARA (UiTM) Perak Branch Alumni Association with the Sports Unit. This programme is one of the initiatives to promote and strengthen the relationship between UiTM alumni and the communities. This programme indirectly has enhanced the spirit of sportsmanship and volunteerism among participants.